Application of model methods in designing and modernization of built-up areas = Zastosowanie metod modelowych w projektowaniu i modernizacji obszarów zabudowanych - Gnatowska, Renata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Processes of spatial planning and modernization of built-up areas require a complex combination of issues important for the development of sustainable urban structures, such as: ecological constructure, wind climate (Environmental Aerodynamics), land development.
Keywords: planowanie przestrzenne; obszary zabudowane; modernizacja; metody modelowe; spatial planning; built-up areas; modernisation; modelling methods